2018
DOI: 10.1186/s13071-018-2637-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Babesia canis transmission in dogs within 24 h and 8 h of infestation with infected pre-activated male Dermacentor reticulatus ticks

Abstract: BackgroundThis study was designed to assess the ability of fed male Dermacentor reticulatus ticks to transmit Babesia canis to dogs after being detached from previous canine or ovine hosts.MethodsThe study was an exploratory, parallel group design conducted in two trials. All the animals were sero-negative for babesiosis prior to enrolment. In a first trial, donor dogs and donor sheep were infested with Babesia canis infected male and uninfected female ticks for 72 h. The ticks were detached and the second gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…The same applies to R. sibirica, the causative agent of North Asian/Siberian tick typhus (Korshunova 1967). Further successful transmission experiments of pathogens from infected ticks to exposed hosts were carried out for the Palma virus (Labuda et al 1997), Coxiella burnetii (Zhmaeva and Pchelkina 1967b), Anaplasma marginale (Zivkovic et al 2007), and B. canis (Varloud et al 2018). According to Balashov (1972) and the European Centre for Disease Prevention and Control (www.ecdc.europ a.eu/en/tular aemia /facts ), D. reticulatus is also a proven vector of Francisella tularensis, the causative agent of tularaemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same applies to R. sibirica, the causative agent of North Asian/Siberian tick typhus (Korshunova 1967). Further successful transmission experiments of pathogens from infected ticks to exposed hosts were carried out for the Palma virus (Labuda et al 1997), Coxiella burnetii (Zhmaeva and Pchelkina 1967b), Anaplasma marginale (Zivkovic et al 2007), and B. canis (Varloud et al 2018). According to Balashov (1972) and the European Centre for Disease Prevention and Control (www.ecdc.europ a.eu/en/tular aemia /facts ), D. reticulatus is also a proven vector of Francisella tularensis, the causative agent of tularaemia.…”
Section: Resultsmentioning
confidence: 99%
“… 2007 ), and B. canis (Varloud et al. 2018 ). According to Balashov ( 1972 ) and the European Centre for Disease Prevention and Control ( www.ecdc.europa.eu/en/tularaemia/facts ), D. reticulatus is also a proven vector of Francisella tularensis , the causative agent of tularaemia.…”
Section: Resultsmentioning
confidence: 99%
“…After attachment to an initial dog host, ticks were observed to move two days after infestation, with 13.3–46% of the R. sanguineus ticks that were present on the initial dog hosts transferring to other co-housed dogs. In a more recent study, two authors of this manuscript [ 32 ] demonstrated the ability of adult D. reticulatus males to reattach to a new host after having been attached to an initial host (sheep or dog) for 72 and 88 h, with a mean rate of reattachment to the second host (dog) of 58% (29/50) and 47% (23/50), respectively. In such situations, where female-seeking male ticks move between hosts, it is possible that they acquire pathogens from infected former hosts.…”
Section: Evidence For Interrupted Feeding In Ticksmentioning
confidence: 99%
“…transmission. However, several studies report that larvae, nymphs, and adult ticks whose blood feeding has been interrupted and who have access to a new host will readily reattach and resume feeding [ 19 , 28 , 29 , 30 , 31 , 32 ]. Termed “interrupted feeding”, the ability of partially fed ticks to survive, reattach to a new host, and complete engorgement is supported by their ability to switch their salivary gland gene expression pattern as demonstrated in Rhipicephalus appendiculatus ticks [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence and distribution of each species of Babesia are closely related to distribution of its vector. B. canis canis is transmitted by Dermacentor reticulatus [10,11], B. canis vogeli is transmitted by Rhipicephalus sanguineus and B. gibsoni is mainly transmitted by Haemaphysalis longicornis and Rhipicephalus sanguineus ticks [12]. Tick is the definitive host for Babesia species where the sexual replication of the protozoa occurs in its intestinal lumen then sporozoits move to salivary gland of the tick till infection of animals occur during tick bites [13].…”
Section: Introductionmentioning
confidence: 99%